2012
DOI: 10.1007/s12664-012-0248-3
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy and strength of agreement between endoscopic ultrasound and histopathology in the staging of ampullary tumors

Abstract: EUS had a moderate strength of agreement with histopathology for both T and N staging, and a high diagnostic accuracy for nodal staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 25 publications
2
24
2
6
Order By: Relevance
“…Among these, 14 studies ( n = 422) that met the inclusion criteria were included in the present analysis. All of the 14 studies were published as full‐text articles in peer‐reviewed journals . Not all studies provided data for all sections; we used the available data for ampullary tumor only.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, 14 studies ( n = 422) that met the inclusion criteria were included in the present analysis. All of the 14 studies were published as full‐text articles in peer‐reviewed journals . Not all studies provided data for all sections; we used the available data for ampullary tumor only.…”
Section: Resultsmentioning
confidence: 99%
“…All EUS examinations were conducted by a single endosonographer except in four, where two or more endosonographers carried out EUS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies showed the reliability of EUS for T staging of ampullary neoplasms, these were limited by small sample size, heterogeneity of study design (combining both duodenal and ampullary lesions), or limited comparative analysis of intraductal extension with ERCP and surgical pathology. 5,8,10 …”
mentioning
confidence: 99%